Determining Marriage Timing Based on the Javanese Traditional Calendar: An Islamic Legal Perspective - Salamah (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to understand how the Javanese transmigrant community in Tangsi Village, Lingga Bayu District, Mandailing Natal Regency, practices the use of the Javanese calendar in determining wedding dates. Employing a case study approach, the research integrates sociological analysis with the fiqh concept of ’urf. The findings show that some members of the community continue to rely on the Javanese calendar as a symbolic form of effort to prevent undesirable events that might disrupt the stages of the wedding ceremony, while others have begun to abandon this tradition due to the strong influence of Mandailing culture and a growing shift toward more rational modes of thinking. From the perspective of legal pluralism, the persistence of this practice reflects the coexistence of Javanese customary norms, Mandailing traditions, and Islamic law, all of which interact within the same social sphere. Meanwhile, the theory of ’urf explains that this practice is acceptable in Islamic law as long as it is understood as a social custom that does not contradict the principles of faith and is not believed to determine fate.